Bacteriology of orofacial infection - Rahman, Z.A.A.; Hassan, H.; Bunyarit, S.S. (2005)
Objective: To establish the causative organisms of orofacial infections and their antimicrobial susceptibilities. Patients and Methods: In this retrospective chart review, 416 samples of pus were obtained from 409 patients with orofacial infection attending a dental school between 1994 and 1998 were sent for culture and susceptibility testing. Results: 109 samples grew normal oral flora and 228 samples grew pathogens. No organisms were isolated in 79 samples. The most common pathogens isolated were viridans streptococci (22.4), Staphylococcus aureus (18.4), enteric gram-negative bacteria (20.2), and Pseudomonas aeruginosa (9.7). All strains of viridans streptococci were susceptible to penicillin. Viridans streptococci and Staphylococcus aureus showed good susceptibilities to erythromycin of 85.7 and 87.1, respectively. Of the enteric gram-negative bacteria, 47.8 were resistant to ampicillin. No anaerobic organisms were isolated in this study. Conclusions: The profile of aerobic isolates and their susceptibilities to antimicrobial agents should assist in selecting empirical therapy and directing therapy for orofacial infection. Inclusion of antimicrobial agents against anaerobic bacteria is recommended.